When the Heart and Actions Diverge: The Mediating Role of Engagement in Bridging Cognitive Dissonance Between Environmental Attitudes and Green Behavior - Salsa Prety Febrianty; Waluyo Budi Atmoko; Ariefah Yulandari (YUME : Journal of Management, 2025)
This study investigates the mediating role of cognitive dissonance in the relationship between environmental attitudes and green purchasing behavior. While individuals often express positive attitudes toward environmental sustainability, a consistent gap remains between these attitudes and actual eco-friendly consumption practices. Through quantitative analysis of survey data, the research explores how cognitive dissonance may influence or disrupt the translation of pro-environmental attitudes into green purchasing actions. The findings suggest that cognitive dissonance significantly mediates this relationship, indicating that internal psychological conflict plays a key role in consumer decision-making within the green marketplace. Implications for environmental marketing and behavioral interventions are also discussed. Keywords: Cognitive Dissonance, Environmental Concern, Environmental Attitudes, Purchasing Behavior, Sustainable Consumption